ENHANCING THE SETTLEMENT OF MILD ASSAULT CASES THROUGH PENAL MEDIATION: LAW ENFORCEMENT PRACTICES BY THE WEST LOMBOK RESORT POLICE - NOVITA LISTYANINGRUM; IRPAN SURIADIATA; ABABIL KARHOMA WIJAYA; SIS NANDA KUS ANDRIANTO (LOIS: Jurnal Hukum dan Humaniora, 2025)
Law enforcement addressing small offenses, particularly minor assaults, is increasingly shifting from traditional judicial systems to restorative justice approaches utilizing prison mediation techniques. This study aims to elucidate the functioning of penal mediation at the West Lombok Resort Police level, the legal frameworks that underpin it, and the challenges encountered throughout its implementation. We employed interviews, field observations, and document analyses to obtain the data. The poll results indicate that criminal mediation relies on the mutual agreement of the victim and the perpetrator, with investigators serving as facilitators and overseers of the procedure. This is supported by the Chief of Police Regulation and the principle that investigators possess the autonomy to make independent decisions, as articulated in the Criminal Procedure Code and the Police Law. Punitive mediation incorporates community members, such as village leaders and Bhabinkamtibmas, to leverage local and societal values in problem resolution.